If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(w + -3) + -2 = -4(-6w + 6) + -8w Reorder the terms: 4(-3 + w) + -2 = -4(-6w + 6) + -8w (-3 * 4 + w * 4) + -2 = -4(-6w + 6) + -8w (-12 + 4w) + -2 = -4(-6w + 6) + -8w Reorder the terms: -12 + -2 + 4w = -4(-6w + 6) + -8w Combine like terms: -12 + -2 = -14 -14 + 4w = -4(-6w + 6) + -8w Reorder the terms: -14 + 4w = -4(6 + -6w) + -8w -14 + 4w = (6 * -4 + -6w * -4) + -8w -14 + 4w = (-24 + 24w) + -8w Combine like terms: 24w + -8w = 16w -14 + 4w = -24 + 16w Solving -14 + 4w = -24 + 16w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-16w' to each side of the equation. -14 + 4w + -16w = -24 + 16w + -16w Combine like terms: 4w + -16w = -12w -14 + -12w = -24 + 16w + -16w Combine like terms: 16w + -16w = 0 -14 + -12w = -24 + 0 -14 + -12w = -24 Add '14' to each side of the equation. -14 + 14 + -12w = -24 + 14 Combine like terms: -14 + 14 = 0 0 + -12w = -24 + 14 -12w = -24 + 14 Combine like terms: -24 + 14 = -10 -12w = -10 Divide each side by '-12'. w = 0.8333333333 Simplifying w = 0.8333333333
| (3n-5)(n-6)=0 | | 63-2e=14-9e | | 5-x=10x | | 33=6+3h | | 4e+6=-50-4e | | 5x+3y=182 | | 8+3e=6+e | | 6a+2=7a-1 | | 3e-2=13e-62 | | 9-8g=31 | | -x-8=4x-38 | | xy+2x=300 | | -4-8x+9x=12 | | .33x+10=0.6 | | -6+3y=-15 | | 3e+16=13e-94 | | (2cosx+1)(cosx+1)=0 | | -x^2-4x+32.01=0 | | 60p+50= | | 7u=4u+9 | | (X+7)(x+1)=(x+1) | | 35=-4d+7 | | (x-0.3)+(2x-0.2)+((40+x)-0.25)=274 | | -10(X+1)=8 | | -6x+15=-33 | | 3x-5(x-4)=-8+3x+3 | | 4x-8=4x+-5 | | 45+4x+7+57x=8 | | 2c-4=c+2 | | 4(3x-2)+4(x+1)=100 | | 7a+2a=18-9 | | 2=-3c+26 |